Bovine Ephemeral Fever As A Disease Related To Climate Change - Sendow, Indrawati (Indonesian Bulletin of Animal and Veterinary Sciences, 2013)
Bovine Ephemeral Fever (BEF) is one of arbovirus diseases infecting in ruminants especially cattle and buffaloes, which istransmitted by mosquito vectors. In general, vector borne disease is also related to climate change, that mosquito as a vector will significantly increase when the environment temperature increases. The disease was found in many countries in Asia, Africa and Australia. The clinical sign of the disease such as fever to paralysis causes economical impact to the farmer, eventhough the mortality is very low. This review will discuss the disease in relation to climate change, which affects vector population that spread the disease. The more population of vector is the higher chance of animal to be infected. This condition describes that the spread of BEF will depend on some factors included the increase of vectors, the availability of susceptible host and vector media facilities, climate condition and supportive ecology. This paper will discuss the feature of BEF, mode of transmission, the impact of environment and climate change, disease prevention and control, and other aspects to prevent further economical impact. It will also discuss how to the transmission, prevention and control of disease BEF. The information can be taken as an input for policy makers to prevent BEF infection in Indonesia.Key words: Bovine ephemeral fever, epidemiology, vector, diagnosis, climate change